FAIRY TALE STORIES AS THE CULTURAL GROWER OF LITERACY READING FOR PRIMARY SCHOOL STUDENTS - Siti Mustakimah; Maulida Ajeng Priyatnomo; Muhamad Chamdani (Universitas Sebelas Maret, 2018)
The children's ability on literacy is essential for their ability development and academical achievement. The purposes of this article are 1) describing fairy tale stories, 2) describing the culture of literacy reading, 3) describing fairy to grower of literacy for primary school students. The research method used was literature study. The data was obtained by doing research study towards some literatures, books, reports and notes included the research problems. The results of this research explains about 1) the description of fairy tale stories, 2) the description of the culture of literacy reading, 3)the description of the usage of fairy tale stories as the literacy culture for children in primary school. The conclusion of this research is that fairy tale is fictional, imaginative, morale and understandable story so that it could be used as an alternative in growing the literacy culture particularly literacy reading for primary school students.